Development of a gas diffusion multicommuted flow injection system for the determination of sulfur dioxide in wines, comparing malachite green and pararosaniline chemistries - Oliveira, Sara M. (2010)
A flow system based on the multicommutation concept was developed for the determination of free and total sulfur dioxide in table wines, exploiting gas diffusion separation and spectrophotometric detection. The system allowed the comparison of malachite green and pararosaniline chemistries, using the same manifold configuration. Free and total SO2 were determined within the ranges 1.00-40.0 and 25.0-250 mg L-1, at determination throughputs of 25 and 23 h-1, respectively. Employing the malachite green reaction, detection limits of 0.3 and 0.8mgL-1 were attained for free and totalSO2, respectively. Pararosaniline chemistry provided detection limits of 0.6 mg L-1 for free SO2 and 0.8 mg L-1 for total SO2. Relative standard deviations better than 1.8 and 1.4% were obtained by the malachite green and pararosaniline reactions, respectively. With regard to the two tested chemistries, 18 wines were analyzed and the results achieved by the pararosaniline reaction compared better with those furnished by the recommended procedure.